2012
DOI: 10.1111/j.1095-8649.2011.03208.x
|View full text |Cite
|
Sign up to set email alerts
|

An elasmobranch maternity ward: female round stingrays Urobatis halleri use warm, restored estuarine habitat during gestation

Abstract: The habitat use and movements of the round stingray Urobatis halleri were compared between shallow restored and natural habitats of the Anaheim Bay Estuary (CA, U.S.A.) in relation to water temperature. Restored habitat remained significantly warmer than natural habitat from spring through to autumn. Strong sexual segregation occurred in the restored habitat with mature female U. halleri forming large unisex aggregations in summer, during months of peak seasonal water temperatures, and males only present durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 46 publications
2
51
0
Order By: Relevance
“…As such, it is possible that the sampling area was a pupping and mating ground and that immature and non-pregnant mature females occur in higher proportions within habitats not sampled in the present study. By occupying the shallow waters sampled by the study, pregnant females may increase the proficiency of their gestation (Jirik and Lowe 2012) or limit their interactions with mature males (Knip et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is possible that the sampling area was a pupping and mating ground and that immature and non-pregnant mature females occur in higher proportions within habitats not sampled in the present study. By occupying the shallow waters sampled by the study, pregnant females may increase the proficiency of their gestation (Jirik and Lowe 2012) or limit their interactions with mature males (Knip et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There are no data to assess the optimal temperature range for tiger sharks, although sharks tend to leave a subtropical Australian bay when water temperatures are below 198C (Wirsing et al 2006). In Hawaii, pregnant female tiger sharks may select islands with warmer temperatures to reduce gestation time of embryos, a behavior commonly seen in elasmobranchs (e.g., Jirik and Lowe 2012). Although males selected islands with higher SST, this may mask more fine-scale behavior, with females selecting shallower and warmer coastal habitats adjacent to islands.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies may use field ultrasound and reproductive hormones in blood samples to verify pregnancy across islands, with a predicted October peak in the number of pregnant females (e.g., Jirik and Lowe 2012). Genetic techniques may provide some critical validation, because we would predict that adult females show philopatry to Oahu (e.g., Mourier and Planes 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Given the reported 15 mo gestation period in tiger sharks (Whitney & Crow 2007), we suggest that gravid or recently mated female tiger sharks may be using the Tiger Beach area in part to benefit from the year-round calm warm water, which likely reduces the gestation period and accelerates embryo development. For example, while not directly measured in the current study, warm water use for gestation has been observed in several other species of gravid elasmobranchs (e.g Bansemer & Bennett 2009, Jirik & Lowe 2012, Nosal et al 2014. Furthermore, the lack of males and dominance of females at Tiger Beach may reduce mating attempt harassment by males (Sims et al 2001, Jacoby et al 2010, Wearmouth et al 2012.…”
Section: Discussionmentioning
confidence: 97%